TECHNOLOGICAL INNOVATIONS AS A FACTOR IN THE COMPETITIVENESS OF INDUSTRIAL ENTERPRISES (FEATURES AND PROBLEMS OF IMPLEMENTING ECONOMIC REFORMS IN AZERBAIJAN, 2025)
In order for enterprises to operate efficiently and be competitive, it is necessary to use tools that will contribute not only to high-quality work, but also to its further development, and technological innovations are one of such tools. In recent years, technological innovations have become a tool for expanding the capabilities of enterprises and achieving their economic goals, they are aimed at creating completely new products or improving existing products. Therefore, industrial enterprises should pay attention to technological innovations in order to make their development sustainable and competitive. From this point of view, the topic of the article is distinguished by its relevance. The main goal of the article is to study technological innovations as the main factor in the success of the competitiveness of industrial enterprises, to determine the benefits that they can give to the activities of these enterprises. The article considers the impact of technological innovations on the competitiveness of industrial enterprises as one of the main types of innovations, investigates the problems that may arise in the field of their application and ways to solve these problems, gives recommendations. done in this regard. The article is mainly written using such methods of analysis as factor analysis, development dynamics, economic and statistical analysis, grouping, generalization.Key words: innovation, innovative activity, technological innovation, competitiveness, industrial enterprises, production.